2015
DOI: 10.1039/c5cc02386f
|View full text |Cite
|
Sign up to set email alerts
|

Simple access to β-trifluoromethyl-substituted ketones via copper-catalyzed ring-opening trifluoromethylation of substituted cyclopropanols

Abstract: Tertiary cyclopropanols react rapidly with Togni reagent in methanol at room temperature in the presence of catalytic amounts (3 mol%) of CuCl affording β-trifluoromethyl ketones in 65-73% isolated yields. Ring opening in 1,2-dialkylsubstituted cyclopropanols gives a mixture of isomeric β-trifluoromethyl ketones in about 50% combined yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 55 publications
4
36
0
Order By: Relevance
“…It has been shown that radical promoted cyclopropanol ring opening tends to break bond “b” to provide more stable and more substituted β-alkyl radical 14 and formation of metallo-homoenolate favors breaking bond “a” to generate less substitute metallo-homoenolate. 10c,11b In our case, the more substituted Walsh bond “b” was selectively cleaved and the difluoroalkylation occurred at the more substituted carbon, which indicates a radical cyclopropanol ring opening process. The selectivity is excellent for the cases of aryl substituted cyclopropanols and products 13a-c were produced as the dominant products.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…It has been shown that radical promoted cyclopropanol ring opening tends to break bond “b” to provide more stable and more substituted β-alkyl radical 14 and formation of metallo-homoenolate favors breaking bond “a” to generate less substitute metallo-homoenolate. 10c,11b In our case, the more substituted Walsh bond “b” was selectively cleaved and the difluoroalkylation occurred at the more substituted carbon, which indicates a radical cyclopropanol ring opening process. The selectivity is excellent for the cases of aryl substituted cyclopropanols and products 13a-c were produced as the dominant products.…”
mentioning
confidence: 60%
“…10d,e We have developed copper-catalyzed cyclopropanol ring opening electrophilic cross-coupling reactions to synthesize various β-CF 3 , β-SCF 3 , and β-amino-substituted carbonyl products. 11a,b Herein, we report novel and unprecedented copper-catalyzed cyclopropanol ring opening alkyl-alkyl cross-coupling reactions with difluoroalkyl bromides, perfluoroalkyl iodides, monofluoroalkyl bromides, and 2-bromo-2-alkylesters as electrophiles (Scheme 1C). In addition to the catalytic nature, the selectivity of breaking the strained Walsh bond of unsymmetrical cyclopropanols is opposite from the previous cases, 10c, 11b which presumably due to a radical ring opening process of the cyclopropanols.…”
mentioning
confidence: 99%
“…Kurzaufsätze quently,the M n ÀX species are oxidized under strong oxidative conditions into the high-oxidative M n+2 À X species.U pon single-electron transfer (SET) an alkoxy radical (H)i s achieved at the same time as the release of M n+1 À X.W elldesigned strategies combining metal catalysts, XÀYreagents, and oxidants have enabled the groups of Narasaka, [20] Murakami, [21] Zhu, [22] Loh, [23] Duan, [24] Zhang, [25] Lopp, [26] and Orellana, [27] to achieve aw ide range of deconstructive functionalizations of cycloalkanols.A na lternative protocol was reported by Chiba, [28] where an alkoxy radical (J)w as added to av inyl azide.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…The ring‐opening strategy could also be employed in the synthesis of distal fluoroalkyl ketones, some recent examples of which were reported by the groups of Dai, Lopp, and Xu (Scheme ). In Dai's method, both trifluoromethylation and trifluoromethylthiolation of cyclopropanols could be realized, although these reactions tended to take place at the less substituted carbons, in contrast to the previous fluorination reactions.…”
Section: One‐step Syntheses Of Distally Fluorinated Ketonesmentioning
confidence: 99%
“…Although mechanistic pictures of these transformations are not very clear at present, Lopp and co‐workers proposed a hybrid mechanism, whereby both electrophilic and radical ring‐opening pathways operate (Scheme ). Initially, the reaction of CuCl with 3,3‐dimethyl‐1‐(trifluoromethyl)‐1,2‐benziodoxole (Togni reagent) yields Cu III complex A , which undergoes ligand exchange with the cyclopropanol and followed by an electrophilic attack of the Cu III center to generate a β‐metalloketone intermediate B .…”
Section: One‐step Syntheses Of Distally Fluorinated Ketonesmentioning
confidence: 99%